Obtention of the mechanical properties of the adobe masonry using (lab based) experimental tests - Catalán Quiroz, Policarpo; Moreno-Martínez, Jatziri Yunuén; Galván, Arturo; Arroyo Matus, Roberto (Acta Universitaria, 2019)
The results from experimental tests applied to a random group of adobe piers and square wallets are depicted in this paper. The process involved in the making of adobe pieces, test pieces, the tests specifications, the analysis of results and characterization of the main mechanical properties of adobe, such as: elasticity modulus, compressive, shear and flexional strength, are described in this paper. This, due to the fundamental need of a code, because currently does not exist, to perform the experimental tests in this type of material, highlighting that 50% of the population in developing countries live in land constructions. The main features of adobe houses in Guerrero (Southeastern zone of Mexico), their construction materials, and the structural components of the typical households in this zone of Mexico are also described in the paper It was concluded that 40% of the maximum compression stress specified in the Mexican Testing Code NMX for calculating the elasticity modulus and the shear modulus does not represent the value that should be used for adobe masonry. This is because the adobe maintains its elastic branch in values of approximately 15%-20% the value of the maximum compression stress.